Approximation of New Sequence of Integral Type Operators with two Parameters (JOURNAL OF ADVANCES IN MATHEMATICS, 2020)
In our paper, we provide and study a new sequence of positive and linear operators of integral type. This sequence depends on two parameters, positive integers and. We mention some of the properties of this sequence and describe a Voronovskaja type asymptotic formula. Besides, we find the error estimates of this approximation in terms of the modulus of continuity. lastly, we introduce a numerical example and compare the results obtained.